2020
DOI: 10.1021/acs.jafc.0c03978
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Lipid and Protein Oxidation in Whey-Protein-Stabilized Emulsions Using a Natural Antioxidant: Black Rice Anthocyanins

Abstract: The food industry is exploring the natural environment to identify botanical extracts that can be used as functional ingredients that can replace synthetic ingredients in foods. In the present study, the ability of black rice anthocyanins as natural antioxidants to inhibit both lipid and protein oxidation in protein-stabilized oil-in-water emulsions was examined. Whey-proteinstabilized emulsions were prepared containing 0, 0.02, 0.04, and 0.06% (w/v) anthocyanins, and then the impact of this plant-based extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 50 publications
5
27
0
Order By: Relevance
“…This effect may be due to the physical binding of FSEY/TBHQ to the surfaces of the adsorbed emulsifier. Our observations are in good agreement with those reported by Yi et al [ 34 ] and Cheng et al [ 35 ], who found that the addition of anthocyanins and flaxseed polyphenols into oil-in-water emulsions resulted in a reduction in the absolute value of ζ-potential. Furthermore, changes in the surface potential during storage are indicative of changes in the interfacial composition.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…This effect may be due to the physical binding of FSEY/TBHQ to the surfaces of the adsorbed emulsifier. Our observations are in good agreement with those reported by Yi et al [ 34 ] and Cheng et al [ 35 ], who found that the addition of anthocyanins and flaxseed polyphenols into oil-in-water emulsions resulted in a reduction in the absolute value of ζ-potential. Furthermore, changes in the surface potential during storage are indicative of changes in the interfacial composition.…”
Section: Resultssupporting
confidence: 93%
“…The FESY-mediated inhibition of these processes may be attributed to its ability to sequester oil drops. The presence of the antioxidants at the interface phase may enhance the repulsive forces between oil droplets, thereby improving their stability [ 34 ]. However, to our dismay, the tetrapeptide could not be stained by Nile blue or FITC (fluorescein isothiocyanate); thus, it cannot be observed by LSCM.…”
Section: Resultsmentioning
confidence: 99%
“…For example, traditional medicine in China uses pigmented rice to prevent anemia and to improve blood circulation, kidney function, and eyesight [29], while black porridge rice is given to aid recovery of broken bones [23]. Recently, Asian KJ CMU 107 BB 3 CMU YMCB 3 CMU 0.5 cm The anthocyanin-rich rice grains have been recognized as excellent sources of natural and safe food colorants [19][20][21]. Synthetic colorants can be harmful to humans and the environment via allergic and toxic reactions [22]; this can raise the demand for naturally pigmented rice such as purple rice that contains high concentrations of anthocyanin.…”
Section: Purple Rice's Market and Trendmentioning
confidence: 99%
“…Bread made from anthocyanin-rich purple rice improved postprandial plasma glucose and antioxidant status in healthy subjects [130] Anthocyanin-rich purple rice flour can be used as a gluten-free ingredient in bread providing FRAP antioxidant activity [131] Bread fortified with 1-4% of anthocyanin-rich rice powder has a low digestion rate that provides health benefits [132] Anthocyanin-rich rice beverage added with xanthan gum has high thermal stability [133] Germinated purple rice that retains anthocyanins has good sensory characteristics [134] Crispy rice bar made purple rice provides high anthocyanin [135] Fresh germinated purple rice noodles provide total anthocyanin and DPPH and FRAP antioxidant capacity [136] 15% of anthocyanin-rich purple rice extract supplemented pasta contains high anthocyanins and antioxidant capacity (DPPH and FRAP) [137] Purple rice sprouts present high total anthocyanin and could be developed for natural health products [138] 0.25% of anthocyanin-rice purple rice extract supplemented yogurt suppresses postprandial glucose level and improved plasma antioxidant capacity in healthy volunteers [19] 0.06% of purple rice anthocyanin extract inhibited lipid and protein oxidation in whey-protein-stabilized food emulsions [21] Other Purposes…”
Section: Functional Foodmentioning
confidence: 99%
See 1 more Smart Citation